Asymmetric price adjustments under ever-increasing costs: evidence from the retail gasoline market in Colombia (2008)
There is abundant empirical evidence showing that asymmetric price adjustments exist in a wide variety of markets. Prices tend to grow faster when costs rise relative to the rate at which prices drop when costs fall. The objective of this paper is to empirically test whether asymmetric price adjustments exist in a scenario where costs are increasing every period. The Colombian retail gasoline market offers an excellent case study due to a specific regulation, something discussed further in this paper. Our results suggest that when costs rise above the reference price -a government suggested retail price- retail prices tend to rise less relative to when costs grow below the reference price. Thus, asymmetry does exist.